Grafu pārlūkošana tīmekļa pārlūkā - Rilins, Aleksandrs (Latvijas Universitāte, 2014)
Strauji attīstoties Informācijas Tehnoloģijām, pieaug arī iegūto datu apjoms, līdz ar to kļūst arvien sarežģītāka arī šo datu analizēšana un attēlošana. Viens no veidiem kā attēlot datus, ir izmantojot grafus, padarot vajadzīgo informāciju uzskatāmāku un ērtāku pārlūkošanai. Lai atvieglotu grafu analizēšanu līdz šim tika izstrādāti vairāki risinājumi, toties pārsvarā tie ir darbvirsmas lietotnes, kuras liedz lietotājiem pilnvērtīgi piedalīties datu izvietošanā un modificēšanā. Darba mērķis ir izpētīt grafu attēlošanas, pārlūkošanas un veidošanas iespējas tīmekļu pārlūkos, ar to saistītas problēmas un veidus kā nodrošināt sadarbību ar jau pieejamajiem un turpmāk veidotajiem rīkiem. Papildus tika apskatīti esošie risinājumi, grafu aprakstīšanas valodas, kā arī tika piedāvāts savs problēmu risinājums un izstrādāts risinājuma prototips.

Every day, the IT industry has to deal with an ever-growing amount of data. It is of no surprise that the analysis and exploration of this data becomes a non-trivial problem, which requires huge time resources. One option to ease this task is to visualize this data as a graph, making information more appealing for researchers. Graph analysis is one of the most complicated problems in computer science and multiple attempts were made to visualize graphs and help people in graph exploration. However, most of the solutions developed by different companies and research labs rely on some specific computer platform and enforce their own work flow. Providing only a static image of necessary data and limiting user participation in the creation, modification and positioning of this data. The main goal of this work is to explore possibilities of visualizing, exploring and creating graphs in modern web browsers and provide compatibility with existing and upcoming tools. Furthermore, the author will discuss languages used for graph and related data structure description, review existing tools for graph visualizing and provide his own solution to the matter. Additionally, a prototype implementing these ideas is developed in the practical part of this paper.
Graph viewing in the internet browser
Keywords: Datorzinātne